Scheduling Framework for Bandwidth-Aware Job Grouping-Based Scheduling in Grid Computing - Keat, Ng Wai; Fong, Ang Tan; Chaw, Ling Teck; Sun, Liew Chee (Malaysian Journal of Computer Science, 2006)
In recent years, Grid computing has emerged as an evolution from the existing distributed computing systems for delivering information, resources and services to users. This new computational infrastructure offers a remarkable increase in the number of available computation capabilities that can be delivered to applications. Grid computing is increasingly being used for aggregating resources across different geographical places. Therefore, job scheduling in the Grid computing environment has posed new challenges which demand for better computing performance and well-improved utilization of resources. This paper investigates the use of bandwidth-awareness in a scheduling framework to enhance the performance of job scheduling.